Solving theoretical and empirical conundrums in international strategy research: Linking foreign entry mode choices and performance - Martin, Xavier (Journal of International Business Studies, 2013)
Several theoretical and empirical developments in the literature on foreign entry mode and performance, and on (international) strategy more generally, were influenced or prefigured by Brouthers’ (2002) JIBS Decade Award winning paper. Regarding theory, Brouthers is an archetype of the integration of transaction cost and institutional perspectives. I argue that it is also relevant to the growing literature that aims at synthesizing these and other perspectives. Methodologically, Brouthers (2002) contributed several uniquely direct and rich measures. Furthermore, it not only displayed awareness of endogeneity (specifically self-selection) issues, but also was among the pioneers in the comparative analysis of governance choices for a given firm or transaction. I elaborate on the promising if challenging use of such “what if” imputation to identify the impact of more or less well-aligned choices. Overall, I argue that such methodological advances cannot be decoupled from the conceptual advances that enable them, and which they reinforce.